2021
DOI: 10.3390/molecules26113219
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Mechanical Properties of Esterified Lignin in Various Polymer Blends

Abstract: Lignin is an abundant polymeric renewable material and thus a promising candidate for incorporation in various commercial thermoplastic polymers. One challenge is to increase the dispersibility of amphiphilic lignin in lipophilic thermoplastic polymers We altered Kraft lignin using widely available and renewable fatty acids, such as oleic acid, yielding more than 8 kg of lignin ester as a light brown powder. SEC showed a molecular weight of 5.8 kDa with a PDI = 3.80, while the Tg of the lignin ester was conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Pure PBS has the lowest density of 1.26 g/cm 3 among all of the composites produced in this study. After the addition of lignin and KCF, all of the composites displayed a higher density compared to pure PBS, where the highest density of 1.43 g/cm 3 was recorded in the PBS70/L30 sample.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 97%
See 1 more Smart Citation
“…Pure PBS has the lowest density of 1.26 g/cm 3 among all of the composites produced in this study. After the addition of lignin and KCF, all of the composites displayed a higher density compared to pure PBS, where the highest density of 1.43 g/cm 3 was recorded in the PBS70/L30 sample.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 97%
“…As one of the main components in lignocellulosic biomasses, lignin is a cheap, readily available and natural substance that has huge potential to be used in bio-based material production [2]. Kraft lignin is mainly found in black liquor, a by-product generated excessively during the paper pulping process and delignification process of both softwoods and hardwoods [3]. Annually, an estimated of 1 million tons of spent pulping liquor were generated by the relevant industries all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…Gioia et al reported the synthesis of an epoxy resinbased on fractionated and subsequently epoxidated KL crosslinked with a polyetheramine. [10] Jawerth et al have investigated the allylation of fractionated KL that allows the reaction with a set of poly-thiols-based crosslinkers to yield materials with tunable mechanical properties. [11] Different esterification strategies to yield thermosets have also been investigated in the production of thermosetting polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The solid nature of lignin and its poor solubility hinders the direct generation of a prepolymer, that is, an important intermediate for the production of a thermoset. A cross‐linking mixture (CLM) is generally not able to disperse KL sufficiently where usually one or more pretreatment steps are required, for example, KL fractionation, KL pre‐functionalization, use of dispersants such as PEG or solvents [10–18] . Consequently, a synthetic strategy that allows the direct mixing of KL and a CLM to yield a uniform liquid prepolymer would be beneficial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation